Hox genes are essential for the development of eyespots in Bicyclus anynana butterflies - Matsuoka, Yuji (Genetics, 2020)
The eyespot patterns found on the wings of nymphalid butterflies are novel traits that originated first in hindwings and subsequently in forewings, suggesting that eyespot development might be dependent on Hox genes. Hindwings differ from forewings in the expression of Ultrabithorax (Ubx), but the function of this Hox gene in eyespot development as well as that of another Hox gene Antennapedia (Antp), expressed specifically in eyespots centers on both wings, are still unclear. We used CRISPR-Cas9 to target both genes in Bicyclus anynana butterflies. We show that Antp is essential for eyespot development on the forewings and for the differentiation of white centers and larger eyespots on hindwings, whereas Ubx is essential not only for the development of at least some hindwing eyespots but also for repressing the size of other eyespots. Additionally, Antp is essential for the development of silver scales in male wings. In summary, Antp and Ubx, in addition to their conserved roles in modifying serially homologous segments along the anterior–posterior axis of insects, have acquired a novel role in promoting the development of a new set of serial homologs, the eyespot patterns, in both forewings (Antp) and hindwings (Antp and Ubx) of B. anynana butterflies. We propose that the peculiar pattern of eyespot origins on hindwings first, followed by forewings, could be due to an initial co-option of Ubx into eyespot development followed by a later, partially redundant, co-option of Antp into the same network.